Fundamentals of Hydrates and Drilling Mud - Lal, B. (Springer Nature, 2022)
This chapter is structured to provide basic principles and general processes on hydrates formation behavior and drilling mud properties. The kinetics and thermodynamic properties of hydrate formation are discussed to reflect the aspects of hydrate formation properties cold be controlled in drilling mud. Also, the types of hydrate drilling mud systems are discussed to provide knowledge on their application for hydrate control during drilling. Â© 2022, The Author(s), under exclusive license to Springer Nature Switzerland AG.